2014
DOI: 10.1057/ejdr.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

Trapped in Agriculture? Credit Constraints, Investments in Education and Agricultural Employment

Abstract: The basic neo-classical model implies that agricultural employment responds positively to increases in farm income. This argument is assumed by proponents and critics of agricultural subsidy programs in their discourse in favor of or against government support for farmers. However, empirical evidence on the relationship between agricultural employment and farm income (and subsidies) is mixed, and some studies find evidence that an increase in farm income has a negative impact on agricultural employment. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Barkley, 1990;Petrick and Zier, 2012) and yet others find a negative impact (e.g. Petrick and Zier, 2012;Berlinschi et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Barkley, 1990;Petrick and Zier, 2012) and yet others find a negative impact (e.g. Petrick and Zier, 2012;Berlinschi et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Hence, (an increase in) subsidies may have an indirect negative impact on agricultural employment because of capital or land substitution, which can (depending on the country and/or time period) dominate the direct positive impact (the direct income effect). Berlinschi et al (2014) propose a related explanation based on education and longer-term adjustments. By increasing farmers' income, subsidies allow credit constrained farmers to invest more in their children's education and thereby their employment choices in the next generation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact information asymmetries have been found to curtail the ability of microfinance institutions to achieve their poverty reduction objectives (Annim 2012). It is possible that agricultural subsidy programs for credit-constrained farmers end up as sources of household income for investing in areas such as children's education-as has been the case in parts of Europe (Berlinschi et al 2014)-rather than improving access to credit. Therefore in order to determine areas in which public investments can be made to sustainably increase access to credit by poor households, it is imperative to understand the factors that influence their access to it.…”
Section: Introductionmentioning
confidence: 99%
“…In Finland, a partial transfer of agricultural subsidies to regional investments increased both regional GDP and employment (Hyytiä 2014). Barkley (1990), Petrick and Zier (2012), and Berlinschi et al (2014) found that CAP had mixed or negative impacts on agricultural employment. In contrast, e.g.…”
Section: Introductionmentioning
confidence: 99%